Digital Resource Management and Student Learning Outcomes in Higher Education: The Mediating Role of Intellectual Capacity - Lilian Anthonysamy; Victor Alasa; Sofia Ali (Journal of Learning for Development)
The shift to hybrid learning during the Covid-19 pandemic emphasised the need for independent learning and effective digital resource management (RMS). This study, grounded in Social Cognitive Theory, examines how RMS supports students in managing digital distractions and optimising learning outcomes. Data from 275 randomly selected education students were analysed using structural equation modeling. Findings indicate that while time management was crucial, other factors like study environment and help-seeking did not directly influence intellectual capacity. Intellectual capacity played a mediating role, linking RMS with perceived learning outcomes. These insights highlight the significance of cognitive strategies in navigating technology-enabled education.